Sposób wyliczenia kwoty podatku akcyzowego na samochody osobowe sprowadzane z państw członkowskich Unii Europejskiej - Dasek, Tomasz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2015)
One of the requirements to import a passenger car to your country is to pay the excise duty also called the excise tax. In this paper the author discusses the most interesting issues for the car purchaser because he will explain the method of calculating the excise duty, which is how much the owner of the imported car has to pay excise tax. The concepts related to this topic will be explained, for example the tax base and rates of excise duty on cars. The author also presents his own observationon the issues discussed.
Keywords: podatek akcyzowy; akcyza; samochody osobowe